IGF‐1 Regulates Vertebral Bone Aging Through Sex‐Specific and Time‐Dependent Mechanisms. (3rd September 2015) - Ashpole, Nicole M; Herron, Jacquelyn C; Mitschelen, Matthew C; Farley, Julie A; Logan, Sreemathi; Yan, Han; Ungvari, Zoltan; Hodges, Erik L; Csiszar, Anna; Ikeno, Yuji; Humphrey, Mary Beth; Sonntag, William E
ABSTRACT: Advanced aging is associated with increased risk of bone fracture, especially within the vertebrae, which exhibit significant reductions in trabecular bone structure. Aging is also associated with a reduction in circulating levels of insulin‐like growth factor (IGF‐1). Studies have suggested that the reduction in IGF‐1 compromises healthspan, whereas others report that loss of IGF‐1 is beneficial because it increases healthspan and lifespan. To date, the effect of decreases in circulating IGF‐1 on vertebral bone aging has not been thoroughly investigated. Here, we delineate the consequences of a loss of circulating IGF‐1 on vertebral bone aging in male and female Igf f/f mice. IGF‐1 was reduced at multiple specific time points during the mouse lifespan: early in postnatal development (crossing albumin–cyclic recombinase [Cre] mice with Igf f/f mice); and in early adulthood and in late adulthood using hepatic‐specific viral vectors (AAV8‐TBG‐Cre). Vertebrae bone structure was analyzed at 27 months of age using micro–computed tomography (μCT) and quantitative bone histomorphometry. Consistent with previous studies, both male and female mice exhibited age‐related reductions in vertebral bone structure. In male mice, reduction of circulating IGF‐1 induced at any age did not diminish vertebral bone loss. Interestingly, early‐life loss of IGF‐1 in females resulted in a 67% increase in vertebral bone volume fraction, as well as increased connectivity density and increased trabecular number. The maintenance of bone structure in the early‐life IGF‐1–deficient females was associated with increased osteoblast surface and an increased ratio of osteoprotegerin/receptor‐activator of NF‐κB‐ligand (RANKL) levels in circulation. Within 3 months of a loss of IGF‐1, there was a 2.2‐fold increase in insulin receptor expression within the vertebral bones of our female mice, suggesting that local signaling may compensate for the loss of circulating IGF‐1. Together, these data suggest the age‐related loss of vertebral bone density in females can be reduced by modifying circulating IGF‐1 levels early in life. © 2015 American Society for Bone and Mineral Research.